Preserving the Beauty of Lake Toba (Environmental of Contextual Theology) - Simanjuntak, Pahala Jannen (LPPM IAKN Tarutung, 2022)
As a member of the church in Indonesia, we are the part of God's people throughout the world. Together receiving the great commission as found in Matt. 28:16-20. In order to realize God's plan, namely the plan of peace through all of His creation. So, as Christians in Indonesia, they realize that they are God's ambassadors and make positive and constructive contributions as a result of their faith in Jesus Christ. No matter how small it is, it will be beneficial in life as a Christian as well as a citizen. In fact, society and the church are burdened and called to restore its beauty. For a long time, the previous parents have enjoyed its beauty until now. But it cannot be denied that Lake Toba currently needs the attention of Lake Toba lovers and even all people who have seen the beauty of Lake Toba long ago. The presence of contextual theology in Indonesia will provide a clearer understanding of the meaning of the Bible in everyday life. In fact, contextual theology has been applied in the lives of God's people from the Old Testament to the New Testament.